Protein interactors of the cellular tumor antigen p53 with response to ionizing radiation - Vásquez, Silvia (2014)
TP53 interacts with the genes CDKN1A, CSNK1A1, CSNK1D, BAX, ATM, MDM2, HIF1A,SP1. This consensus network has many binding regions involved in phosphorylation. To find whether or not the interactions are involved in ionizing radiation (IR), we used protein interaction mining and visualization tools to decipher the network. We conclude that ATM, PCNA, TP53 and CDKN1A show protein interactions on cellular response to IR.